Multimodal holographic microscopy: distinction between apoptosis and oncosis - Balvan, Jan; Krizova, Aneta; Gumulec, Jaromir; Raudenska, Martina; Sladek, Zbysek; Sedlackova, Miroslava; Babula, Petr; Sztalmachova, Marketa; Kizek, Rene; Chmelik, Radim; Masarik, Michal (PloS one, 2015)
Identification of specific cell death is of a great value for many scientists. Predominant types of cell death can be detected by flow-cytometry (FCM). Nevertheless, the absence of cellular morphology analysis leads to the misclassification of cell death type due to underestimated oncosis. However, the definition of the oncosis is important because of its potential reversibility. Therefore, FCM analysis of cell death using annexin V/propidium iodide assay was compared with holographic microscopy coupled with fluorescence detection - "Multimodal holographic microscopy (MHM)". The aim was to highlight FCM limitations and to point out MHM advantages. It was shown that the annexin V+/PI- phenotype is not specific of early apoptotic cells, as previously believed, and that morphological criteria have to be necessarily combined with annexin V/PI for the cell death type to be ascertained precisely. MHM makes it possible to distinguish oncosis clearly from apoptosis and to stratify the progression of oncosis.
Keywords: multimodální zobrazování; apoptóza; Holography; lidé; holografie; Apoptosis; Cell Line, Tumor; fenotyp; Cell Survival; Phenotype; Humans; Necrosis; fluorescenční mikroskopie; nekróza; viabilita buněk; Time Factors; Microscopy, Fluorescence; nádorové buněčné linie; časové faktory; Multimodal Imaging